Ultrasound‐guided fine needle aspiration diagnosis of supraglottic laryngeal cancer1. Issue 2 (8th August 2011) - Lopchinsky, Richard A.; Amog‐Jones, Glenda F.; Pathi, Renuka; Kraus, Dennis H.
Abstract Background.Although intraoperative laryngoscopic examination and biopsy of patients who present with locally advanced supraglottic carcinomas remains the standard of care, there are occasions when a more expedited biopsy can be helpful. Methods and Results.We describe a quick diagnostic technique of ultrasound‐guided fine needle aspiration of endolaryngeal advanced supraglottic carcinomas, which can be performed in the clinic without any preparation. Ultrasound scanning is performed through the thyrohyoid membrane. The tumor is visualized as an irregular hypoechoic mass. While continuing to visualize the mass, a 21‐gange needle attached to a syringe is passed through the contralateral thyrohyoid membrane into the mass. Suction is applied, and the aspirate is sent for cytologic study. Conclusions.When formal intraoperative laryngoscopy and biopsy is not feasible or timely, ultrasound‐guided fine‐needle aspiration biopsy enables a rapid diagnosis and eliminates the cost, side effects, and risks of a direct laryngoscopy. © 2011 Wiley Periodicals, Inc.† Head Neck, 2013